Aploneura lentisci (Homoptera: Aphididae) and Its Interactions with Fungal Endophytes in Perennial Ryegrass (Lolium perenne) - Popay, Alison J.; Cox, Neil R. (Frontiers in Plant Science, 2016)
Aploneura lentisci Pass. is endemic to the Mediterranean region where it is holocyclic, forming galls on its primary host, Pistacia lentiscus and alternating over a 2-year period between Pistacia and secondary hosts, principally species of Gramineae. This aphid is widely distributed in Australia and New Zealand on the roots of the common forage grasses, ryegrass (Lolium spp.) and tall fescue (Schedonorus phoenix) where it exists as permanent, anholocyclic, parthenogenetic populations. Previous studies have indicated that infestations of A. lentisci significantly reduce plant growth and may account for differences in field performance of Lolium perenne infected with different strains of the fungal endophyte Epichloë festucae var. lolii. These obligate biotrophs protect their host grasses from herbivory via the production of alkaloids. To confirm the hypothesis that growth of L. perenne is associated with the effect of different endophyte strains on aphid populations, herbage and root growth were measured over time in two pot trials that compared three fungal endophyte strains with an endophyte-free control. In both pot trials, aphid numbers were lowest on plants infected with endophyte strain AR37 at all sampling times. In plants infected with a common toxic strain naturalized in New Zealand, aphid numbers overall were lower than on uninfected plants or those infected with strain AR1, but numbers did not always differ significantly from these treatments. Populations on AR1-infected plants were occasionally significantly higher than those on endophyte-free. Cumulative foliar growth was reduced in AR1 and Nil treatments relative to AR37 in association with population differences of A. lentisci in both trials and root dry weight was reduced in one trial. In four Petri dish experiments survival of A. lentisci on plants infected with AR37 declined to low levels after an initial phase of up to 19 days during which time aphids fed and populations were similar to those on plants without endophyte. Aphids on AR37-infected plants became uncoordinated in their movement and developed tremors before dying suggesting a neurotoxin was responsible for their mortality. Results support the hypothesis that differences in A. lentisci populations due to endophyte infection status and strain affects plant growth.